ANALYSIS OF THE EFFECT OF SATISFACTION ON EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE WORK MOTIVATION AT JATAYU BAKERY KRIAN SIDOARJO - Moch Nur Halim Halim; Syahirul Alim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of job satisfaction on employee performance mediated by work motivation at Jatayu Bakery Krian Sidoarjo. Job satisfaction is one of the key factors that determine the level of motivation and employee performance within an organization. In the context of the food and beverage industry, which is characterized by fast-paced work and high accuracy demands such as at Jatayu Bakery, the level of employee satisfaction becomes a major determinant of productivity and work quality. The population in this study consists of all employees of Jatayu Bakery Krian Sidoarjo, totaling 60 people. The sampling technique used is saturated sampling (census) since the population size is relatively small and all members were included as respondents. The results of the study show that job satisfaction has a positive and significant effect on work motivation, meaning that the higher the employee’s satisfaction, the greater their motivation to work. In addition, work motivation is proven to have a positive and significant effect on employee performance, indicating that motivation is an important factor in improving productivity. Furthermore, job satisfaction also has a positive and significant effect on employee performance, both directly and indirectly through the mediation of work motivation. These findings indicate that work motivation acts as a partial mediating variable in the relationship between job satisfaction and employee performance at Jatayu Bakery Krian Sidoarjo. Therefore, the management of Jatayu Bakery is expected to continuously enhance job satisfaction through the provision of incentives, a comfortable working environment, and opportunities for self-development so that both motivation and employee performance can continue to improve sustainably.